Ligand-Free CuI-Catalyzed Chemoselective S-Arylation of 2-Mercaptobenzimidazole with Aryl Iodides - Tan, Bryan Yong-Hao; Teo, Yong-Chua (Synlett, 2018)
A practical and efficient strategy for the chemoselective C–S cross-coupling of 2-mercaptobenzimidazole derivatives with a range of substituted aryl iodides is described. Under the optimized conditions of 5 mol% CuI and 100 °C, a variety of S-arylated products were obtained in good to excellent yields (up to 92 %) without the need for assisting ligands.
Keywords: 2-mercaptobenzimidazole; ligand-free; S-arylation; copper(I) iodide; chemoselective